2022
DOI: 10.1038/s41419-022-05292-9
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 induction via the MEK-JNK-AP1 axis by a neddylation inhibitor promotes cancer-associated immunosuppression

Abstract: MLN4924 is a first-in-class small molecule inhibitor of NEDD8-activating enzyme (NAE), which is currently in several clinical trials for anti-cancer applications. However, MLN4924 also showed some off-target effects with potential to promote the growth of cancer cells which counteracts its anticancer activity. In this study, we found that MLN4924 increases the levels of PD-L1 mRNA and protein in dose- and time-dependent manners. Mechanistic study showed that this MLN4924 effect is largely independent of neddyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…It has been reported that inactivation of NAE1 and UBA3 or pevonedistat treatment promoted PD-L1 expression in glioblastoma, lung cancer, and pancreatic cancer cells through c-MYC, ERK1/2, or JNK pathway. 35 , 36 In contrast, pevonedistat did so in ATLL cells through STAT3 activation. Although p-STAT3–driven PD-L1 mRNA expression seems to be a common mechanism among natural killer/T-cell lymphomas cells, ALK + ALCL cells, and ATLL, 11 , 17 , 18 each disease might have a distinct mechanism for STAT3 activation, as illustrated by pevonedistat and ruxolitinib, which affected P-STAT3 in ATLL cells but not in ALK + ALCL cells.…”
Section: Discussionmentioning
confidence: 93%
“…It has been reported that inactivation of NAE1 and UBA3 or pevonedistat treatment promoted PD-L1 expression in glioblastoma, lung cancer, and pancreatic cancer cells through c-MYC, ERK1/2, or JNK pathway. 35 , 36 In contrast, pevonedistat did so in ATLL cells through STAT3 activation. Although p-STAT3–driven PD-L1 mRNA expression seems to be a common mechanism among natural killer/T-cell lymphomas cells, ALK + ALCL cells, and ATLL, 11 , 17 , 18 each disease might have a distinct mechanism for STAT3 activation, as illustrated by pevonedistat and ruxolitinib, which affected P-STAT3 in ATLL cells but not in ALK + ALCL cells.…”
Section: Discussionmentioning
confidence: 93%
“…Pevonedistat (MLN4924, TAK924) is a small molecule inhibitor of NEDD8. Pevonedistat blocks the degradation of the PD-L1 protein by inhibiting Cullin3 activity [ 64 , 65 ], increasing the levels of PD-L1 mRNA and protein in a dose- and time-dependent manner [ 66 ]. (Fig.…”
Section: Preclinical Study Of Ptms Inhibiting Pd-l1 Expression and Fu...mentioning
confidence: 99%
“…Beyond its anticipated therapeutic effects in targeted therapy, MLN4924 has demonstrated certain unintended consequences that may foster cancer cell proliferation. These outcomes are primarily associated with the activation of intracellular ERK and JNK signaling, leading to activator protein-1 activation ( 133 ). Simultaneously, the inhibitory effects of MLN4924-induced neddylation suppression can upregulate T-cell negative regulator programmed death-ligand 1 (PD-L1) expression ( 134 ).…”
Section: Exploration Of Neddylation As a Potential Molecularly Target...mentioning
confidence: 99%
“…Cancer cells exhibiting a high expression of PD-L1 can attenuate T-cell cytotoxicity through the activation of the PD-1/PD-L1 axis, inducing immune suppression ( 135 ). Combining anti-PD-L1 antibodies or mitogen-activated protein kinase inhibitors with MLN4924 administration offers a potential avenue to address these challenges effectively ( 133 ).…”
Section: Exploration Of Neddylation As a Potential Molecularly Target...mentioning
confidence: 99%